Spore Density and Viability of Entomopathogenic Fungal Isolates from Indonesia, and Their Virulence against Aphis gossypii Glover (Homoptera: Aphididae) - Siti Herlinda (Tropical Life Sciences Research, 2010)
The focus of this study was on quantifying fitness attributes, such as spore density and viability, and determining the virulence level against aphid (Aphis gossypii) nymphs of isolates from the fungal species Beauveria bassiana and Metarhizium anisopliae. The fungal isolates were obtained from several insects, including Plutella xylostella, Hypothenemus hampei, Bronstispa longissima, A. gossypii, Tenebrio molitor, and Leptocorisa acuta, that were collected from Indonesian islands, such as Sumatera, Java, and Sulawesi. Third instar aphid nymphs were inoculated via topical application of 106 conidia ml–1 of the entomopathogenic fungal isolates. All of the B. bassiana and M. anisopliae isolates could produce very dense spores. The M. anisopliae isolate MaAg, which was obtained from the aphid, had the highest spore density at 6.70 x 108 conidia ml–1 . Among the B. bassiana isolates, the highest conidial viability belonged to isolate CPJW8, which was obtained from Chrysodeixis chalcites, with a 39% average viability. Among the M. anisopliae isolates, the highest viabilities belonged to the isolates MaAg and MaLa, which were obtained from L. acuta, with a 33% and 32% average viabilities, respectively. All of the B. bassiana and M. anisopliae isolates were virulent against aphid nymphs, with mortality rates ranging from 64% to 94%. The three most virulent isolates were BBY715 (94%), MPx (92%), and MaTm (92%), and the least virulent isolate was MaLa (64%). BBY715, the most virulent isolate, had the shortest lethal time median (LT50) against aphid nymphs at 2.97 hours, and MaLa had the longest LT50 at 61.81 hours. Tujuan kajian ini adalah untuk mengukur ciri-ciri keafiatan, seperti kepadatan dan keupayaan hidup sendiri spora, menentukan tahap kebisaan pencilan spesies kulat Beauveria bassiana dan Metarhizium anisopliae terhadap nimfa aphid (Aphis gossypii). Pencilan kulat tersebut didapatkan dari pelbagai species serangga, termasuk Plutella xylostella, Hypothenemus hampei, Bronstispa longissima, A. gossypii, Tenebrio molitor, dan Leptocorisa acuta, yang dikumpulkan dari pulau-pulau di Indonesia, iaitu Sumatera, Jawa, dan Sulawesi. Nimfa instar ketiga aphid diinokulasikan secara topikal dengan konidia pencilan kulat entomopatogen dengan kepadatan 106 konidia ml–1. Kesemua pencilan-pencilan B. bassiana dan M. anisopliae dapat menghasilkan konidia dengan kepadatan yang sangat tinggi. Pencilan M. anisopliae MaAg, yang didapatkan dari aphid, memiliki kepadatan spora paling tinggi iaitu 6.70 x 108 konidia ml–1 . Di antara pencilan B. bassiana, keupayaan hidup sendiri konidia paling tinggi dimiliki oleh pencilan CPJW8, yang berasal dari Chrysodeixis chalcites, dengan purata keupayaan hidup sendiri sebanyak 39%. Di antara pencilan M. anisopliae, keupayaan hidup sendiri paling tinggi dimiliki oleh pencilan-pencilan MaAg and MaLa, yang berasal dari L. acuta, dengan purata keupayaan hidup sendiri sebanyak 33% dan 32% masing-masing. Semua pencilan B. bassiana dan M. anisopliae menjangkiti nimfa aphid, dengan tahap kematian antara 64% hingga 94%. Tiga pencilan yang paling berbisa menjangkiti aphid adalah BBY715 (94%), MPx (92%), dan MaTm (92%), dan yang paling lemah adalah MaLa (64%). BBY715, pencilan yang paling berbisa menjangkiti aphid, memiliki lethal time median (LT50) paling singkat terhadap nimfa aphid, iaitu 2.97 jam, dan MaLa memiliki LT50 paling lama iaitu 61.81 jam.